Assessment of Poland’s national parks in Tripadvisor users’ reviews - Osóch, Barbara; Zbaraszewski, Wojciech (Economics and Environment, 2025)
Nature tourism, including tourism in protected areas, is becoming increasingly important. Since protected areas are traditional and popular tourist destinations, it is advisable that opinions posted about them online should be studied. The article analyses the opinions of visitors to Polish national parks posted on Tripadvisor.com by May 2023. The ranking created shows which of these valuable natural areas are visited in which seasons and by which target groups. The study points to evident seasonality of visitation, associated with the warmer part of the year in most of the parks, and shows that the groups of visitors come mainly from Poland and the neighbouring countries. It is noted that, based on visitor ratings, some national parks are visited by tourists from all over Europe and while others attract mainly Poles. The scope of the study is limited by the incomplete data obtained for the national parks (with no reviews retrieved for 4 national parks, i.e., Tatra, Białowieża, Świętokrzyski, Ojców). The method used was adapted to achieve the goal of the study, which was to identify and analyse Tripadvisor.com users' opinions on Polish national parks. Users’ reviews are an invaluable source of information, informing subsequent choices made by other travellers visiting the parks.